2022
DOI: 10.1002/humu.24424
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potential novel candidate genes in schwannomatosis patients

Abstract: Schwannomatosis comprises a group of hereditary tumor predisposition syndromes characterized by, usually benign, multiple nerve sheath tumors, which frequently cause severe pain that does not typically respond to drug treatments. The most common schwannomatosis‐associated gene is NF2, but SMARCB1 and LZTR1 are also associated. There are still many cases in which no pathogenic variants (PVs) have been identified, suggesting the existence of as yet unidentified genetic risk factors. In this study, we performed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…LZTR1 had been studied mostly with respect to their functions in the nervous system, such as schwanmomatosis [ 9 ], autism [ 10 ], and Noonan syndrome [ 11 , 12 ]. However, in 2017, Cancer Genome Atlas Research Network published the results of the comprehensive and integrative genomic characterization in hepatocellular carcinoma (HCC), and they found that LZTR1 was the significantly mutated gene in HCC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…LZTR1 had been studied mostly with respect to their functions in the nervous system, such as schwanmomatosis [ 9 ], autism [ 10 ], and Noonan syndrome [ 11 , 12 ]. However, in 2017, Cancer Genome Atlas Research Network published the results of the comprehensive and integrative genomic characterization in hepatocellular carcinoma (HCC), and they found that LZTR1 was the significantly mutated gene in HCC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…2. Of note, SMARCA4- [6] and DGCR8- [7,8] schwannomatosis represent two recent forms of schwannomatosis, without any specific clinical features, and might constitute rare events [9].…”
Section: Key Pointsmentioning
confidence: 99%